Determining Purchase Decisions: Analysis of Green Marketing and Digital Marketing (Marketing Management Literature Review) - M. Rizky Mahaputra; Farhan Saputra; Raihan Saputra (Siber Nusantara of Economic and Finance Review, 2024)
The purpose of writing this Literature Review Paper is to determine the influence of green marketing and digital marketing variables on purchasing decisions. Using qualitative methods and Library Research. The research results show that green marketing influences purchasing decisions, digital marketing influences purchasing decisions, green marketing and digital marketing together influence purchasing decisions.